Self-perceive on food allergy prevalence among university student in Selangor - Tengku Azhar, Tengku Norbaya; Mohd Idris, Siti Noorfahana; Abdul Ghani, Radiah; Che Hassan, Muhammad Rahimi; Mohamed, Malissa; Mohd Zazi, Norhafizah; Haridan, Umi Shakina; Abd Wahab, Noor Akmal (2019)
Prevalence of allergy is a worldwide issue. The outbreak contributes to social and economic burden of the sufferer as well as the society. In Malaysia, the condition has continued to worsen due to the misconception of certain allergy symptom such as food allergy versus food intolerance. It also lead to improper clinical diagnosis which effect treatment accuracy and upturn the cost of the treatment. This circumstances are corresponded to the level of public awareness and knowledge about the term, signs and symptom of allergy prevention. This study aimed to highlight the allergy prevalence among young adult based on self–perceive approach. This cross-sectional study involved 138 respondents of students with the age of 18 to 19 years old from Centre of Foundation Study, UiTM Cawangan Selangor, Kampus Dengkil. Overall, the allergy prevalence reported within the study population comparatively to another self-perceive and clinical data from previous study showed the higher occurrence. The data indicated that n=80 (58%) of respondents facing allergy problems indicating seafood such as shrimp as the most common implicated food allergen with n=43 (31.25%) followed with house dust mite with n=40 (29%)and peanuts with n=14 (10.1%). Pearson correlation between respondent’s knowledge of allergy term, cause and symptom with allergy prevention and treatment shows weak highly significant correlation with (r = 0.387, P<0.001). Chi Square Test among students with allergies who were getting consultation with health personnel shows significant association (P<0.001) in which 41 (59.4%) of students with allergies do not consult with health personnel. The study also specified the shortcoming of the self- perceive approach due to the symptom misinterpretation and the quality of the survey instrument. As a conclusion self-perceive only, is useful to give surface overview on allergy prevalence, but detail clinical diagnosis is compulsory to ensure the effectiveness of allergy prevention and treatment in future.